Pengaruh Motivasi Kerja, Beban Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan di Perusahaan Bekasi - Sri Wahyuningsih; Catur Sasi Kirono (Journal on Education, 2023)
This study aims to determine the effect of Motivation, Workload, and work environment on Employee Performance at PT Hitachi Astemo Bekasi Break System, the research method used is quantitative with a sample of 56 respondents at PT Hitachi Astemo Bekasi Break System. The sampling technique uses purposive sampling. The results showed that partial work motivation (X1) had a significant positive influence on performance, the better the work motivation, the better the performance received. The workload variable (X2) has a significant positive influence on performance, the more the workload increases, the more it will improve employee performance. The work environment variable (X3) has a significant positive effect on performance, the more the work environment increases, the more it will improve employee performance. Simultaneously, there is a significant positive influence on employee performance.